Factors controlling the distributions of dissolved organic matter in the East China Sea during summer - Kim, Jeonghyun (Sci Rep, 2020)
To determine the distribution of dissolved organic matter (DOM) in the East China Sea (ECS) during the summer, we measured the dissolved organic carbon (DOC) and nitrogen (DON), fluorescent dissolved organic matter (FDOM), and chlorophyll a (Chl. a) in the upper 100-m layer of this region during July and September 2015. The DOC (r(2) = 0.72 and 0.78 in July and September, respectively) and DON (r(2) = 0.43 and 0.33) were significantly correlated with salinity, suggesting that the river is the primary origin of DOM. However, we found that at a DOC “pulse” under a salinity ranging from 24 to 35, the extrapolating DOC values (304 ± 11 μM) were twice higher than those with a salinity of close to 0, as found in a previous study. The excess DOC concentration seemed to be attributed to the microbial metabolism during transport from the estuary based on the good relationships between DOC and marine humic-like FDOM (r(2) = 0.42 and 0.47), as well as the fluorescence, humification, and biological indexes, but showed no correlation with Chl. a. Thus, the results of our study indicate that microbial activities can be a significant factor controlling the distribution of DOM in the ECS during summer.